Relationship Between Costs and Returns in the Rainfed Kharif Crops on Arid Lands - Singh, D V; Mathur, B K (Annals of Arid Zone, 2016)
Agriculture in arid region is purely a gamble on rainfall. Farmers decision to minimise the expenditure on cost of cultivation, in the environment of risk and uncertainty. may thus be justified. It is difficult to visualise the impact of cost on returns in these circumstances. Correlation coefficient estimated to measure the relationship between cost and returns is found weak. The cost is not fully reflected in returns and tells very little what shall be the level of returns for a given amount of cost.